Microwave application in micronizing wet fermented cocoa beans - Hussein, H.; Ibrahim, Mohd Nordin; Ab. Aziz, Norashikin; Ismail, A. (Faculty of Engineering, Universiti Putra Malaysia, 2016)
The application of microwave in the micronizing process of the wet fermented cocoa beans was investigated using commercially available domestic microwave oven. Fermented wet beans at four different levels of moisture content were micronized using three levels of microwave power. The four levels of the fermented wet beans moisture content were 43.5%, 31.1%, 21.9% and 12% wet basis; while the microwave power were selected based on the three pre-setting configurations, i.e.; Low, Medium and High. In order to prevent the final product from being scorched, burnt and exposed to excessive hot spots, the microwave power was introduced intermittently during the micronizing process. The effect of the micronizing process on the separation efficiency of nibs and shells was determined using three parameters. The parameters were the percentage of nibs in shells (NiS%), the percentage of shells in nibs (SiN%), and the percentage of un-retrieved beans (U%). The effect of the micronizing on the nib’s final moisture content and the bean temperature was also recorded. The results showed that for wet beans with 21.9% and 12% moisture contents, the separation effect in terms of the percentage of nibs in shell (NiS%) was below the allowable value when micronized at three levels of microwave power. However, the effect of the percentage of shells in nibs (SiN%) was found to be lower than the allowable value for all four wet beans moisture levels micronized at the three microwave power. On the other hand, the amount of un-retrieved beans (U%) was found to be in the range of 28.3% to 2.28% for wet beans with moisture contents of 43.5% and 31.1%, when micronized at the three microwave power levels. The nibs final moisture content for wet beans moisture of 31.1% and 21.9% were 3.80+0.39 and 2.59+0.07 respectively, when micronized with high microwave power and these values were found to be not significantly different (p>0.05) with the control. A similar result was obtained when wet beans with 12% moisture was micronized at low and medium power. The temperature of the beans was determined to be in the range of 108ᴼC to 260ᴼC during this test.